Comparison of physical performance measures of flexibility, strength & balance of school students with university students - Mishkat Fatima, Saba Riaz, Syeda Nimra Amir, Sahar Shoaib, Maheera Saleem, Laiba Imran, Laiba Amir (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: To find out variation in flexibility, strength and balance of university and school students on their dominant and non-dominant sides. Study Design: A Cross section study. Place and duration of study: Data was collected from Lahore grammar school (LGS), Al’Ala school and university of management and technology (UMT), Lahore. After approval of synopsis (RE-092-2021) the data collection was done from the duration of 10th November 2021 to 15th February 2022. Methodology: A cross section study conducted on healthy school and university students. The data was collected by non-probability convenient sampling. After verbal Informed consent the data was obtained from school students of grade 7-10 from Lahore Grammar school and Al’Ala international Islamic school and undergraduate’s students of UMT by using convenient sampling. Physical performance tests for measuring strength (sit-ups), flexibility (Zipper, sit and reach, dorsiflexion) and balance (Flamingo test) were demonstrated and were asked to perform. Readings were taken of each test. Results: Sit ups excellent results were reported in majority of university students (36%). Sit and reach test was found better in university (32%), zipper test positive results were better in school students. Dorsiflexion test normal values were more in university (18%). Flamingo test showed 45% university students had good balance. There was statistically significant difference in zipper (P=0.004), flamingo (P=0.036) on non-dominant side and sit and reach dominant (P=0.006) and non-dominant side (P=0.031). Practical implication: The normative data of physical performance measures can help prevent injuries, as these can be used as a reference to detect poor health and lethargy at school and university level. These measures can be used as a reference for primary prevention among university going and school going students. Furthermore, to increase awareness about physical fitness among young population. Conclusion: Both groups showed good physical performance measures. Flexibility test showed better results in School students. Strength test showed better result in university students whereas, balance test reported better in school students. Keywords: Balance, Flexibility, Limb dominance, musculoskeletal injuries, Physical activity, Strength,